PD-1 Is Elevated on the Peripheral Blood T Cell Subsets of Patients with Relapsed/Refractory Hodgkin Lymphoma Compared to Normal Volunteers - Diefenbach, Catherine S.; Sabado, Rachel; Clark-Garvey, Sean; Cruz, Crystal; Vengco, Isabelita; Rojas, Celeste N; Serrano, Victoria; Zain, Jasmine M.; Cho, Hearn J.; O'Connor, Owen A. (Blood, 2011)
Abstract 4860 Programmed death-1(PD-1) and programmed death-1 ligand (PD-L) signaling are involved in the functional impairment and “exhaustion” of T cells in conditions such as chronic viral infection and in tumor immune evasion. The interaction of PD-1 with its ligand PD-L suppresses T cell function. Up-regulation of PD-L has been demonstrated both in Hodgkin lymphoma (HL) cell lines, and in primary Hodgkin Reed Sternberg (HRS) cells. PD-1 is markedly elevated in the tumor infiltrating lymphocytes of HL patients, leading to the hypothesis that T cell exhaustion and deficient anti-tumor immunity induced by the activation of the PD-1-PD-L signaling pathway may play a key role in creating a permissive milieu for HL. In this setting, elevated PD-1 expression in HL patient T cells may be a biomarker of disease activity. We investigated this hypothesis by examining PD-1 expression in the peripheral T cells of patients with relapsed/ refractory HL. Patients with relapsed or refractory HL who enrolled in a clinical trial of an HDAC inhibitor in combination with Niacinamide between December of 2010 and July of 2011 were eligible to participate. PD-1 levels were assessed pre-treatment, and at selected timepoints during therapy. The levels of PD-1 expression for 5 relapsed/refractory HL patients and 4 healthy control subjects were evaluated by flow cytometry. An aliquot of cells (1 × 106/mL) was washed and stained with: CD3 APC-H7, CD8 PerCP-Cy5.5, CD4 FITC and PD-1-APC, for 20 minutes at 4°C. Dead cells were excluded using the Live/Dead Fixable Staining Kit (Invitrogen), and stained cells were acquired using the LSR II flow cytometer (BD). Compensation (parallel controls using cells singly stained for each color) and data analysis were performed using FlowJo flow cytometry analysis software (TreeStar). The percentage and/or mean fluorescence intensity (MFI) of PD-1+ cells within the live CD3+CD4+ and CD3+CD8+ populations was compared to isotype controls to establish baseline values and to normal control subjects. The median age of the 5 HL patients was 32 (range 25–73). The median age of the healthy control subjects was 43 (range 39–49). Three of the HL subjects were male; all 4 of the normal controls were female. All 5 of the HL patients were heavily pretreated with an average number of prior regimens of 7.8 (range 5–13). Three of the 5 patients underwent previous autologous stem cell transplant, and 2 had a prior allogeneic stem cell transplant. There was a clear shift of PD1+ cells within the CD4+ T cell population in the HL patients compared to normal controls. PD-1 was significantly elevated in the peripheral blood CD4+ cells of HL patients compared to normal volunteers (mean MFI 1034 vs 123, p < 0.025). PD-1 was also elevated on the CD8+ T cells of the HL patients compared to normal volunteers (MFI 808 vs 221), but did not reach significance. There was no correlation between the level of PD-1 elevation on CD4+ or CD8+ cells, and prior autologous or allogeneic transplantation. PD-1 expression in peripheral blood CD4+ T cells may be a potential biomarker of systemic immune dysregulation in heavily pre-treated HL patients. PD-1 warrants further exploration in relapsed/refractory HL both as a potential biomarker, and as a target for directed immunotherapy. Additional studies by our group, investigating the role PD-1 as a biomarker in relapsed/refractory HL are ongoing. O'Connor:Spectrum: Research Funding; Novartis: Research Funding; Merck: Research Funding; Celgene: Consultancy, Research Funding.